Hispanic-Serving Institutions and Web Accessibility: Digital Equity for Hispanic Students With Disabilities in the 21st Century. (October 2021) - Taylor, Z. W.; Burnett, Christopher A.
The Americans with Disabilities Act (ADA) mandates that all Title IV-participating institutions of higher education publish web accessible websites for students with disabilities. This study sought to evaluate the web accessibility of Hispanic-Serving Institutional (HSI) websites ( n = 217). Results suggest that the average HSI website landing page included 447 errors, violating ADA. Most errors were related to font size, color contrast, and hyperlinks and pictures. Implications for research, practice, and support for Hispanic students with disabilities are addressed.